Boulder shores in South Africa – a distinct but poorly documented coastal habitat type. Issue 2 (3rd April 2017) - Tucker, L; Griffiths, CL; Schroeter, F; Vetter, HD
Abstract : This study compares the composition, species richness and biomass of macrofaunal and algal assemblages on intertidal boulder shores as compared with those on adjacent rock-platforms, at six sites along the southwest coast of South Africa. Of 214 species identified, 175 were recorded on boulder shores and 124 on rock-platform shores; of these, 99 species were common to both habitat types, 92 were exclusive to boulders, and 23 were exclusive to rock-platforms. Significant differences in community structure ( F (1, 95) = 13.02, p < 0.01) (PERMANOVA test), species richness ( F (1, 95) = 14.28, p < 0.01), biomass ( F (1, 95) = 9.45, p < 0.01) and diversity ( F (1, 95) = 578.83, p < 0.01) (two-way ANOVA) were detected between the two habitat types. Average dissimilarity of community structure between rock-platform and boulder shores was 87.96% (SIMPER analysis). The increased species richness and biomass on boulder shores extended across all tidal levels, but was most marked in the highshore. These results confirm that boulder shores along the southwestern Cape support a distinct biota, richer and very different from that on adjacent rock-platforms, and rich in boulder-dependent species. We propose that boulder shores merit separate management and conservation targets as compared to rock-platforms, though the ecology of boulder shores in the region remains very poorly known and requires further study.